2019
DOI: 10.1002/slct.201803820
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Esterification to Glyceryl Diacetate over SO42−/W‐Zr Complex Solid Super Acid Catalysts

Abstract: A series of SO42−/W−Zr catalysts with different W/Zr mole ratios were synthesized by solvent evaporation self‐assembly followed by impregnation of sulfuric acid. The catalysts were examined in the glycerol esterification with acetic acid, and fully characterized by XRD, BET, TEM, XPS, NH3‐TPD, H2O‐TPD and pyridine adsorption infrared spectroscopy. The results revealed that W/Zr mole ratio and calcination temperature significantly affected the structure, acidity and catalytic performance of the catalysts. SO42−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…2. As can be seen, all samples exhibit two correlating distinctive peaks at 3432 and 1620 cm − 1 , which are attributed to the vibration of the hydroxyl ring in the catalyst and water [21]. All samples' peaks at 507 and 747 cm − 1 are attributed to the distinctive peaks of crystalline ZrO 2 in the meanwhile [22].…”
Section: Characterization Of Catalystmentioning
confidence: 81%
See 1 more Smart Citation
“…2. As can be seen, all samples exhibit two correlating distinctive peaks at 3432 and 1620 cm − 1 , which are attributed to the vibration of the hydroxyl ring in the catalyst and water [21]. All samples' peaks at 507 and 747 cm − 1 are attributed to the distinctive peaks of crystalline ZrO 2 in the meanwhile [22].…”
Section: Characterization Of Catalystmentioning
confidence: 81%
“…1. The pure ZrO 2 sample exhibits the diffraction peaks at 2θ value, which is according with tetragonal phase and monoclinic phase ZrO 2 [19][20][21]. It could be found that the peaks ascribed to monoclinic phase after acidi cation with sulfuric acid were receded.…”
Section: Characterization Of Catalystmentioning
confidence: 95%
“…Subsequently, sulfate groups were incorporated by the incipient wetting impregnation method with H 2 SO 4 . The best results were obtained with the solid presenting W/Zr = 1 ratio and calcined at 500 • C, due to the presence of a high number of acid sites and a good tolerance to the presence of water [141].…”
Section: Glycerol Esterification With Acetic Acidmentioning
confidence: 99%